Studying the developments of clouds and rainfall over Western Ghats, India: High Altitude Cloud Physics Observatory in Rajamallay, Munnar - E A Resmi; R K Sumesh; V C Mobin Raj; G R Malavika; A R Aswini; C T Tejavath; P P Leena; S Nita; C K Unnikrishnan; K Sreelash; S Sneha; D Jash; et al. (Journal of Earth System Science, 2026)

Hydrometeor categorization in stratiform and convective precipitation systems over a tropical coastal region - Sumit Kumar; Dharmadas Jash; E. A. Resmi; R. K. Sumesh; Gadha Gopan; Mohit Kumar; Anusha Andrews; Nita Sukumar (Theoretical and Applied Climatology, 2024)

Analysis of localized features during wet and dry rainfall episodes over southern tip of India - E. A. Resmi; B. Preethi; R. S. Ajayamohan; Pallav Ray; C. K. Unnikrishnan; S. Nita; R. K. Sumesh; J. Dharmadas (International Journal of Climatology, 2023)
The large spatial and temporal variability of wet and dry spells of the Indian Summer Monsoon (ISM) poses the great challenge in understanding and predicting monsoonal rainfall. This challenge is further exacerbated over smaller regions, such as the southern tip of India, which receives the first spell of ISM rainfall. In this study, the characteristic features and possible precursors for wet and dry spells of rainfall over the southern tip of India are investigated. We also explore the variability in monsoon low‐level jet (LLJ) in relation to wet and dry spells over a coastal station Thiruvananthapuram (8.48°N, 76.95°E) in southwest India using in situ observations and other ancillary datasets. The results show that a wet spell spanning 3–4 days contributes about 30% of seasonal rainfall. Wet spells are characterized by westerly wind anomaly in the southern tip of India and easterly wind anomaly in northern India, leading to anomalous cyclonic vorticity over the Indian subcontinent. The opposite happens during dry spells. These characteristics are prominent from 2 days prior to the initiation of the spells, suggesting they may be used as precursors for forecasting wet and dry spells over Thiruvananthapuram. Analysis of low‐ to mid‐tropospheric (2 and 4 km) humidity reveals significant moistening (drying) during wet (dry) spells. Yet, both wet and dry spells experience humid (>80%) boundary layer. The differences in mid‐level humidity and thermodynamical structures between wet and dry spells seem to contribute to distinct rainfall characteristics over the southern tip of India. These results indicate that the use of in situ observations along with large‐scale reanalysis datasets may provide valuable information on the precursors for wet and dry spells over the southern tip of India, which can help both in regional‐ and city‐level planning and management of water resources.

Tropical cyclones over north Indian Ocean during El-Niño Modoki years - K. G. Sumesh; M. R. Ramesh Kumar (Natural Hazards, 2013)

Erratum to: Assessing environmental and occupational risk factors for lung cancer in Mexican–Americans - Michelle K. McHugh; Sumesh Kachroo; Mei Liu; Anthony M. D’Amelio; Qiong Dong; Waun Ki Hong; Anthony J. Greisinger; Margaret R. Spitz; Carol J. Etzel (Cancer Causes & Control, 2011)

Assessing environmental and occupational risk factors for lung cancer in Mexican–Americans - Michelle K. McHugh; Sumesh Kachroo; Mei Liu; Anthony M. D’Amelio; Qiong Dong; Waun Ki Hong; Anthony J. Greisinger; Margaret R. Spitz; Carol J. Etzel (Cancer Causes & Control, 2010)